Povezanost biokemičnih označevalcev in ehokardiografskih značilnosti pri karcinoidni srčni bolezni - Ravnik, Maja (Medicinski razgledi, 2001)
Carcinoids are neuroendocrine tumors. They produce physiologically active substances which can cause carcinoid syndrome and carcinoid heart disease at higher concentrations. The characteristic changes seen in carcinoid heart disease are carcinoid endocardial plaques. The pathogenesis of carcinoid heartdisease is not completely understood. An attempt was made to show the differences in biochemical markers between two groups of patients: those with carcinoid heart disease and those without it. Through these differences we hoped to get some insight into the pathogenesis of carcinoid heart disease andto be able to verify the diagnostic value of these biochemical markers. Oneof the objectives was also to calculate the incidence of carcinoid heart disease in patients with carcinoid syndrome in Slovenia. Our hypotheses were as follows: 1. Levels of chromogranin A, 5-HIAA and TGF-beta1 will be significantly higher in the group with carcinoid heart disease compared to thecontrol group. 2. Concentrations of 5-HIAA before treatment with octreotidewill be significantly higher in the group with carcinoid heart disease compared to the control group. 3. Treatment with octreotide will not prevent the appearance of carcinoid heart disease. The study was prospective and included all patients in Slovenia who were diagnosed with and treated for carcinoid syndrome at the time. They were divided into two groups based on echocardiographic findings typical for carcinoid heart disease. Serum concentrations of chromogranin A were measured using RIA, urinary concentrations of 5-HIAA were measured using HPLC, and serum concentrations ofTGF-beta1 were measured using ELISA. Nonparametric tests were used for statistical analysis. (Abstract truncated at 2000 characters).
Keywords: Carcinoid heart disease; Ehokardiografija; Karcinoidna srčna bolezen; Diagnosis; Physiopathology; Tumorski markerji, biološki; Therapy; Karcinoidni tumor; Tumor markers, biological; Okteotid; Diagnostic use; Statistika neparametrična; Echocardiography; tumorski označevalci; Malignant carcinoid syndrome; Octreotide; Statistics, nonparametric; diagnostika